"Ecstasy" to addiction: Mechanisms and reinforcing effects of three synthetic cathinone analogs of MDMA. (1st May 2018) - Dolan, Sean B.; Chen, Zhenglan; Huang, Renqi; Gatch, Michael B.
Abstract: This study aimed to address the mechanisms and reinforcing effects of three synthetic cathinone analogs of MDMA commonly reported in "Ecstasy" formulations: methylone, butylone, and pentylone. Whole-cell patch clamp techniques were used to assess the mechanism of each compound at the dopamine and serotonin transporters. Separate groups of rats were trained to discriminate methamphetamine, DOM, or MDMA from vehicle. Substitution studies were performed in each group and antagonism studies with SCH23390 were performed against each compound that produced substitution. Self-administration of each compound was evaluated under a progressive ratio schedule of reinforcement. Each compound produced an inward current at the serotonin transporter, but little or no current at the dopamine transporter. Each of the test compounds substituted fully for the discriminative stimulus effects of methamphetamine, methylone and butylone substituted partially for DOM and fully for MDMA, whereas pentylone failed to substitute for DOM and substituted only partially for MDMA. SCH23390 fully and dose-dependently attenuated methamphetamine-appropriate responding produced by each test compound, but was least potent against pentylone. MDMA-appropriate responding was minimally affected by SCH23390. Each test compound was robustly self-administered with pentylone producing the greatest self-administration at the doses tested. Given the prevalence of synthetic cathinones in "Ecstasy" formulations, these data indicate that adulterated "Ecstasy" formulations may drive more compulsive drug use than those containing only MDMA. Highlights: MDMA, methylone, butylone, and pentylone are serotonin transporter substrates. Each drug produces methamphetamine-like discriminative stimulus effects. Methylone and butylone produce largely serotonergic discriminative stimulus effects. Pentylone produces predominately dopaminergic discriminative stimulus effects. Pentylone is self-administered to greater degree than butylone or MDMA.